L’Orient bouddhiste d’André Chevrillon - Durand, Jean-François (Romanica Silesiana)
<!–EndFragme–> Jean-François Durand shows the world of primeaval cultures of the colonised countries of Africa and Asia, the world fastly going back to the past at the end of the 19th century, presented by André Chevrillon, a traveller and writer, who tries to preserve the vanishing values, falsified with the ideology of the civilised mission of colonists from the beginning of the conquest, as a result of the acculturation of traditional values, religion, traditions and lifestyle of the conquered nations. Keywords : colonization; Asian and African first cultures; acculturation; André Chevrillon